A Review Paper on Modern Technologies (International Journal of Innovative Research in Engineering & Management, 2021)
The impact of technologies on humans life has completely  took a place in every forms of words as it is in traveling, in  learning or in communication from others and these gadgets  has made our life easy. The technology also help to improve the standards of communications, educations, health-care and  many more. Therefore, many companies have already shifted  to the new technologies and some are planning to move from  offline services to online services. This paper explains that, these technologies have made our life easy and is now became  important in every field. Before the arrival of technologies, everyone gets difficulties in communicating and sharing their  data or views. The growth of internet has increased because  all the facilities are available on every platforms and every  one can excess that easily from everywhere. However, on  other side these are affecting the children because of the  misuse of the internet. So these new technologies have the bad  impacts as well as good impacts on their convince to use the  new technologies. Earlier there is no use of online shopping  everyone goes and buy it traditionally but now mostly  everyone buys it online as per their convince. In future, the  technologies will get vaster from now and have many scopes  to achieve the higher growth.
Keywords: Communication; Education; Human; Medical; Technology